Differences in distribution of the 210 kDa neurofilament subunit and the S-100 protein in the small intestine of a human fetus with trisomy 21 and in that of a normal fetus of the same age - Bagyánszki, Mária (Acta Biologica Szegediensis, 2004)
The enteric nervous system of the small intestine of a 22-week-old male fetus with trisomy 21 was examined and compared with gut specimens from a fetus with normal karyotype at the same developmental stage. After the therapeutic termination of the pregnancies, paraffin sections and whole-mounts were prepared, which were processed for histology and immunohistochemistry, with the use of antibodies against the 210 kDA neurofilament subunit and the glial marker S-100 protein. The reduced length of the small intestine, the histologically observed fewer and shorter villi and the frequently appearing pseudostratified epithelium indicate an overall delay in the intestinal development in the trisomic fetus. Both the S-100 protein-immunopositive glial cells and the neurofilament protein-immunopositive nerve cells were distributed differentially in the gut specimens of the trisomic fetus and in the fetus with normal karyotype. While the immunohistochemical expression of the S-100 protein differed only in the circular axis of the gut wall, the distribution of the neurofilament protein-immunoreactive nerve cells also differed along the longitudinal axis of the gastrointestinal tract. Not only the distribution, but also the morphology of the neurofilament protein-immunoreactive myenteric ganglion cells differed in the trisomic fetus as compared with the normal one. The neurofilament protein-immunopositive ganglion cells of the normal fetus possessed lamellar dendrites and one long axon, while the ganglion cells of the trisomic fetus did not exhibit special morphological characteristics. These observations suggest that the enteric nervous system of the fetus with trisomy 21 is involved in the overall delay of the gut development.